Usage of and attitudes toward heat- and moisture-exchanging breathing devices among adolescent skiers - Stenfors, N.; Hanstock, H.; Ainegren, M.; Lindberg, A. (Translational Sports Medicine, 2021)
Heat- and moisture-exchanging breathing devices (HME) humidify and heat-inhaled air and prevent exercise-induced bronchoconstriction. HMEs have potential as primary preventers against airway damage and asthma induced by exercise in sub-zero temperatures. HME usage among athletes has not been previously investigated. This study surveyed the usage of and attitudes toward HMEs among elite skiers. We invited all 347 students from Swedish National Elite Sports Schools in cross-country skiing and biathlon to participate in a web-survey. The response rate was 55%, 53% were women, 30% had asthma, and 87% were cross-country skiers. Their mean (range) age was 17 (15-19) years. HMEs were used often or occasionally by 71% of respondents, while 68% reported respiratory symptoms while training in sub-zero temperatures. The most common temperature threshold for using HMEs was -15°C. Almost all participants believed that HMEs prevent airway problems induced by training in cold. The participants were motivated, and confident in succeeding, to increase their HME usage during exercise in -10°C or colder, if recommended. Swedish adolescent skiers commonly use HMEs and have positive attitudes toward increased HME usage. HMEs may constitute a simple and effective prevention strategy against airway symptoms and asthma among winter endurance athletes.